1985
DOI: 10.1111/j.1365-2621.1985.tb10579.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites of Eurotium Species, Their Antioxidative Properties and Synergism with Tocopherol

Abstract: Natural antioxidants and synergists for tocopherol (Tot) have been isolated as acetone or ethyl acetate extracts from mycelial mats or culture broth of Ertrorium species. The acetone extract, eluted stepwise with benzene and ethyl acetate by silica gel column chromatography, gave fractions that were synergistic with Tot. However, the benzene fraction appeared better because it was highly soluble in oil and did not change the color and taste of the oil. The metabolites in the benzene fraction differed in the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
0
12
1
Order By: Relevance
“…FG and its related compounds were found to be synergistic agents of the -tocopherol antioxidant in an assay of lipid peroxidation, using the active oxygen method (AOM) and a substrate of lard. 24) However, the isolated antioxidants were shown not to have a synergistic effect, but rather an additive effect in the assay of present study (data not shown). We think that the isolated antioxidants may act in cooperation with -tocopherol, which is contained in arabushi, to inhibit lipid oxidation during the manufacture of karebushi, although the relationship between the antioxidative activity of the isolated antioxidants and -tocopherol in karebushi needs further research.…”
Section: Activity Of the Antioxidants Isolated From Filamentous Fungicontrasting
confidence: 46%
See 1 more Smart Citation
“…FG and its related compounds were found to be synergistic agents of the -tocopherol antioxidant in an assay of lipid peroxidation, using the active oxygen method (AOM) and a substrate of lard. 24) However, the isolated antioxidants were shown not to have a synergistic effect, but rather an additive effect in the assay of present study (data not shown). We think that the isolated antioxidants may act in cooperation with -tocopherol, which is contained in arabushi, to inhibit lipid oxidation during the manufacture of karebushi, although the relationship between the antioxidative activity of the isolated antioxidants and -tocopherol in karebushi needs further research.…”
Section: Activity Of the Antioxidants Isolated From Filamentous Fungicontrasting
confidence: 46%
“…These compounds have also been isolated from extracts of fungi of E. chevalieri IFO4086 and E. repens IFO4041 which were not isolated from katsuobushi. 24) In the present study, they were found to be produced by Eurotium species which were isolated from katsuobushi such as E. chevalieri JCM23047, E. chevalieri NBRC4090, E. repens JCM23060, and E. repens KBN2062. For the first time, antioxidants were found to be abundantly produced from E. herbariorum NE-1 and NE-4 which have long been used to manufacture karebushi, a kind of katsuobushi.…”
Section: Identification Of the Antioxidants Produced By Filamentous Fmentioning
confidence: 52%
“…Aoyama et al (6) isolated the antioxidative phenolic compounds--citrinin, protocatechuic acid and curvulic acid--from fungi. We also have reported that some microbial metabolites are potent antioxidants and Toc synergists in several fat substrates with excellent activity compared to that of Toc alone (9)(10)(11)(12)(13)(14). We also have reported that some microbial metabolites are potent antioxidants and Toc synergists in several fat substrates with excellent activity compared to that of Toc alone (9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Antioxidative substances produced by bacteria, yeast and fungi may serve as antioxidants, synergists, scavengers or lipoxygenase inhibitors and they are also differ in nature. Ishikawa et al (1985) reported that the metabolites (flavoglaucin derivatives) from Eurotium spp. had different antioxidant activity and suggested that the number and the position of the double bond causes instability of each derivative.…”
Section: Antioxidant Activity Production Of Rumen Protozoa and Bacteriamentioning
confidence: 99%